First Americans : U.S. patriotism in Indian country after World War I - Grillot, Thomas (Yale University Press, 2018)
Drawing from archival sources and oral histories, Thomas Grillot demonstrates how the relationship between Native American tribes and the United States was reinvented in the years following World War I. During that conflict, twelve thousand Native American soldiers served in the U.S. Army. They returned home to their reservations with newfound patriotism, leveraging their veteran cachet for political power and claiming all the benefits of citizenship - even supporting the termination policy that ended the U.S. government's recognition of tribal sovereignty. --